2012
DOI: 10.1002/eji.201142162
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced GITR/GITRL interactions augment IL‐27 expression and induce IL‐10‐producing Tr‐1 like cells

Abstract: The glucocorticoid-induced TNFR-related (GITR) protein is a coactivating receptor that is constitutively expressed on Treg cells and induced on activated T cells. To better understand the role of long-term GITR signaling, we generated a mouse that constitutively expresses GITR ligand (GITRL) on APCs that mimics the physiological distribution of GITRL in vivo. Despite a five-fold expansion of the Treg-cell pool, there is increased activation and depletion of naive T cells in the transgenic (Tg) mice, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 26 publications
1
48
0
Order By: Relevance
“…4). Consistent with these data, we observed an increase of both cCD4 + T and Treg cells in the GITRL transgenic mice, accompanied by multiorgan lymphocytic infiltration without any sign of autoimmune disease (27,28), which suggests that the GITR/GITRL interaction regulates the balance between regulatory and effector CD4 + T cells. Our data also indicate that authentic GITR signaling has a dual effect on immune responses-a stimulatory effect on conventional T cells and an inhibitory effect via Treg cells.…”
Section: Discussionsupporting
confidence: 88%
“…4). Consistent with these data, we observed an increase of both cCD4 + T and Treg cells in the GITRL transgenic mice, accompanied by multiorgan lymphocytic infiltration without any sign of autoimmune disease (27,28), which suggests that the GITR/GITRL interaction regulates the balance between regulatory and effector CD4 + T cells. Our data also indicate that authentic GITR signaling has a dual effect on immune responses-a stimulatory effect on conventional T cells and an inhibitory effect via Treg cells.…”
Section: Discussionsupporting
confidence: 88%
“…In wild type mice, 1% of CD4 + T cells in the spleen are FoxP3 − IL-10 + independent of age, whereas in transgenic mice with antigen-presenting cells that constitutively express GITRL, the FoxP3 − IL-10 + subset is 1% in 2 week-old mice and increases to 6%-7% in 12 week-old mice, suggesting that chronic GITR/ GITRL signaling induces the generation/expansion of FoxP3 − IL-10-producing Tr1-like cells [57]. The addition of a neutralizing anti-IL-10 monoclonal antibody (mAb) restored T-cell proliferation in suppression assays, indicating that suppression by the Tr1-like cells was mediated by IL-10.…”
Section: Gitr Is a Crucial Player In Treg Differentiation And Expansionmentioning
confidence: 94%
“…These cells express FoxP3 (at levels lower than CD25 high cells), CTLA-4, IL-10, and TGF-β, and are CD45RA − . Thus, CD4 + CD25 low/− GITR + cells are similar to human Tr1 clones [78] and Foxp3 − IL-10-producing Tr1-like cells expanded in GITRL − transgenic mice [57]. Recently, Tr1 precursor cells were detected in peripheral blood lymphocytes and characterized as CD4 + LAG-3 + CD49b + [79].…”
Section: Gitr May Be More Useful Than Cd25 As a Marker Of Human Tregsmentioning
confidence: 95%
“…30,[32][33][34] It has also been showed that the long-term interactions of GITR/GITRL signaling boosted Tr1-cell differentiation and expansion in mice in vivo. 35 Zohar et al believed that chemokine (C-X-C motif) ligand 11/chemokine receptor 3 (CXCL11/CXCR3) interaction may induce transformation of CD4…”
Section: In Vitro Induction Of Tr1 Cellsmentioning
confidence: 99%